Analisis Kerajinan Boneka Berbahan Koran Bekas Produk Galeri J-ART - Oky Tri Suci Saulaka; Mesra Amirudin Mesra; Daulat Saragi Daulat (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to describe the craft of dolls made from used newspapers from the indicators of shape, and plasticity carried out in the J-Art Gallery. This research is a qualitative descriptive study. The subjects of this study were 3 doll craft works made from used newspapers from J-Art Gallery. The accuracy of the shape of the doll and its plasticity are the objects in this study. Data collection methods used are observation, documentation, and interviews. Analysis of the data used is descriptive qualitative analysis techniques. The results of this study indicate that the accuracy of the shape and plasticity of dolls made from used newspapers on the J-Art Gallery products is quite good. The accuracy of the shape and plasticity of doll products made from used newspapers in the J-Art Gallery have shown the accuracy of the shape and the nature of plasticity that are in accordance with the characters of adult human dolls and also in accordance with consumer interests and support the preservation of regional culture.